Nosocomial or Hospital-acquired Infections-Main Role of Nursing, Health information, Laboratory Professionals, and Health Security Workers - Maslamani, Afnan Essam Mohammad; ALMUTAIRI, MESHARI SALEM NASER; Zaila, Samirah Saddig; alonazey, Sultan ibrahim; albogami , Afaf moadi; Alrashedi, Aisha Nashi; Almotiab , Mona Abdulaziz R; alanazi, Salhah qayad Saad; albariqi, Bader Ahmed Mohammed; Albogami , Haya Mohammed; ARISHI, MOHAMMED HUSSAIN ABDU; ALSAYED, HANI HUSSAN ABED; et al. (Journal of Ecohumanism, 2024)
Background: Hospital-acquired infections (HAIs) remain a significant public health challenge, contributing to increased morbidity, mortality, and healthcare costs. Despite advancements in infection control, HAIs persist due to factors including antimicrobial resistance, immunocompromised patient populations, and lapses in basic hygiene practices. Emerging pathogens such as MRSA, VRE, and Clostridium difficile further complicate prevention efforts, particularly in high-risk settings like ICUs and surgical wards. Aim: This article examines the critical roles of nursing professionals, healthcare information specialists, security personnel, and laboratory practitioners in mitigating HAIs. It evaluates evidence-based interventions, systemic challenges, and future directions for comprehensive infection prevention strategies in diverse healthcare environments. Methods: A comprehensive review was conducted of epidemiological data, national surveillance systems including the NNIS, and infection control guidelines from leading organizations such as the CDC and JCAHO. The analysis incorporated clinical studies, outbreak reports, and peer-reviewed research on multimodal HAI prevention approaches across different healthcare settings. Results: Key findings demonstrate that nursing adherence to hand hygiene and care bundles reduces HAI rates by up to 50%. Healthcare information systems enable critical real-time tracking of infection trends and antimicrobial resistance patterns. Laboratory professionals enhance prevention through rapid pathogen identification and molecular epidemiology, while security teams maintain essential physical and digital safeguards for infection control infrastructure. Persistent challenges include staffing shortages, overcrowding, and inconsistent protocol compliance across facilities. Conclusion: Effective HAI prevention requires integrated, multidisciplinary approaches combining clinical expertise with technological and systemic support. Future strategies must emphasize technological innovation, interprofessional collaboration, and sustain adherence to evidence-based protocols to address evolving microbial threats.